Human Papillomavirus Vaccination uptake and associated factors among schools girls aged between 9–14 years in Ethiopia: Performance Monitoring for Action (PMA-ET) 2023, multilevel analysis - Ermias Bekele Enyew; Mulugeta Desalegn Kasaye; Shimels Derso Kebede; Mahider Shimelis Feyisa; Naol Gonfa Serbessa; Tsion Mulat Tebeje; Abiyu Abadi Tareke (PLoS ONE, 2025)
Background Human papillomavirus (HPV) is one of the sexually transmitted diseases infections that causes cervical cancer, and it is the second-leading cause of infection-related cancer globally. HPV infection causes around 604,000 cervical cancer cases (342,000 deaths) globally each year. Therefore, this study aimed to assess Human Papillomavirus Vaccination uptake and associated factors among schools girls in Ethiopia. Method Performance Monitoring for Action Ethiopia (PMA Ethiopia) is a survey project designed to generate data on various reproductive, maternal, and newborn health (RMNH) indicators that can inform national and regional governments. The prevalence of HPV vaccine uptake with a 95% Confidence Interval (CI) was reported and presented in a forest plot for East Africa Countries using STATA version 14.1. Intra-class Correlation Coefficient (ICC), Likelihood Ratio (LR) test, Median Odds Ratio (MOR), and deviance (−2LLR) values were used for model comparison and fitness. Adjusted Odds Ratios (AOR) with a 95% Confidence Interval (CI) and p-value ≤0.05 in the multilevel logistic model were used to declare significant factors associated with HPV vaccine uptake. Result In Ethiopia, the prevalence of HPV vaccine uptake among schools girls was 30.82% (95% CI: 29.21, 32.45). In the multilevel logistic regression model, girls in age groups of 12–14 years were 2.44 [AOR = 2.44, 95% CI: 1.86–3.16] times more likely to take HPV vaccine as compared to girls aged 9–11 years. Similarly, girls who had received any health service and received sexual and reproductive health services had 7.75 [AOR = 7.75, 95% CI: 5.65–10.62], and 3.24 [AOR = 3.24, 95% CI: 2.33–4.51] were more likely to take HPV vaccine compared to their counterparts respectively. Conclusion The study findings indicate that the proportion of girls reporting receipt of the HPV vaccine in this nationally representative survey is an alarmingly low 30.8%. The following critical factors have influenced this rate: age, access to sexual and reproductive health services, general health service utilization, and regional health disparity.